2019
DOI: 10.29136/mediterranean.486732
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of presence of urban green space in the case of Niğde city

Abstract: Dünya nüfusunda yaşanan artışa bağlı olarak kentsel alanlardaki yapısal unsurlarda da hızlı bir artış meydana gelmektedir. Yapısal unsurlarda ortaya çıkan bu artış kentsel alanlardaki yeşil alanların zaman içersinde azalmasına hatta yok olmasına neden olmaktadır. Özellikle de kentlerin gelişiminde önemli bir yere sahip olan mekânsal planlarda yeşil alanların dikkate alınmaması bu alanların kaybını hızlandırmaktadır. Bu çalışmada, orta ölçekli kent olan Niğde kenti içerisinde yer alan mevcut yeşil alanlar ile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…Supporting this situation, green area studies in Niğde state that structural areas have doubled and green area quantities have halved over a 10-year period [37]. It is also noted that the continuous expansion of the city center with the increase in population adversely affects active green spaces and causes significant damage to the ecosystem [39]. A noteworthy feature of this study is the use of Buffer and Network analysis methods for spatial accessibility assessment.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Supporting this situation, green area studies in Niğde state that structural areas have doubled and green area quantities have halved over a 10-year period [37]. It is also noted that the continuous expansion of the city center with the increase in population adversely affects active green spaces and causes significant damage to the ecosystem [39]. A noteworthy feature of this study is the use of Buffer and Network analysis methods for spatial accessibility assessment.…”
Section: Discussionmentioning
confidence: 79%
“…[38], çalışmasında orta ölçekli bir kent olan Niğde kent merkezinin artan nüfusa paralel olarak yeni konutların artması yerleşim alanını devamlı olarak genişletmekte olduğunu, bu durumun aktif yeşil alanları olumsuz etkilediğine hatta ekolojik yapıya da büyük zarar verdiğini belirlemiştir. [39], çalışmalarında kent merkezinin 589 276.01 m²'lik alana sahip 177 adet aktif yeşil alan olduğu ve kişi başına 4.09 m² aktif yeşil alan düştüğü belirlenmiştir. Çalışma sonucunda kent merkezinde yer alan aktif yeşil alanların yetersiz olduğu tespit edilmiş ve bu alandaki yeşil alanların nicel olarak artışlarını sağlamaları adına öneriler geliştirmiştir.…”
Section: Yılında Yayınlanan 29030 Sayılı Mekânsal Planlar Yapımunclassified
“…Although the playground areas per child are insufficient in the district, it is higher than the results of the research in other cities (Olgun & Yılmaz, 2019;Şişman & Özyavuz, 2010;Türkan & Önder, 2011). It has been found that the playgrounds in the district have significant deficiencies, especially the design and planning problems.…”
mentioning
confidence: 63%
“…The most widely used quantitative indicator to evaluate urban green infrastructure is urban green space per capita (Badiu et al, 2016). In addition to this, studies conducted on urban green space inequalities mostly discuss parameters such as green space per capita, percentage of green space and proximity to urban green space (Yenice, 2012;Olgun & Yılmaz, 2019;Gascon et al, 2016). However, it has been stressed in recent research that the quality and accessibility of green spaces are closely related to criteria such as the size diversity and spatial clustering of the green space (Jim, 2013;Zhou et al, 2018).…”
Section: Methodsmentioning
confidence: 99%